INFLUENCE OF WHITE PEPPER POWDER (Piper nigrum L.) VEGETABLE INSECTICIDE ON PEST MORTALITY OF RICE WEEVILS - Akhmad Gazali; Dewi Arini; Noorkomala Sari; Ilhamiyah Ilhamiyah (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2023)
A reduction in rice quality may result from pest infestations in storage facilities. In addition to being a major pest of rice, the rice weevil (Sitophilus oryzae L.) is a problem in warehouses. Attacks by rice weevils may result in lower-quality rice. Using white pepper powder as a pesticide is one way to solve this issue. The purpose of this study is to ascertain how white pepper powder, a botanical pesticide, affects rice weevil pest mortality, as well as the optimal dosage and mode of administration. In this study, there were six treatments and four replications in a single factor totally randomized design. The rate at which rice weevil bugs died and the percentage of rice weight loss were the study's parameters. The results showed that the death of rice weevil pests was influenced using white pepper powder. The highest mortality rate was L5 at 52.5%, which is the best dose.